Achieving Access to Justice in a Business and Human Rights Context An Assessment of Litigation and Regulatory Responses in European Civil-Law Countries - Rouas, Virginie (OBServing Law, 2022)
Achieving Access to Justice in a Business and Human Rights Context explores the interplay between access to justice and business and human rights- a growing area of international human rights law- in European civil-law countries. Multinational enterprises (MNEs) can contribute to economic prosperity and social development in the countries where they operate. At the same time, their activities may directly or indirectly cause harm to humans and to the environment. However, MNEs are rarely held accountable for their involvement in human rights abuses and environmental damage. In recent years, activists have challenged corporate impunity by introducing innovative claims seeking to hold parent companies directly liable for the harm caused by their group's activities. They have also strategically used this type of litigation to trigger corporate accountability reforms at international, regional, and national levels. Using national litigation experiences as a starting point and focusing on European civil-law countries, the book evaluates the extent to which litigation against MNEs has been effective in achieving access to justice and corporate accountability. It also considers whether ongoing regulatory developments, such as the adoption of mandatory human rights due diligence norms and the negotiations for a business and human rights treaty, can contribute to the realisation of access to justice and corporate accountability in the future.